2022
DOI: 10.1002/advs.202201819
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Bone Tumor and Subcellular Endoplasmic Reticulum via Near Infrared II Fluorescent Polymer for Photodynamic‐Immunotherapy to Break the Step‐Reduction Delivery Dilemma

Abstract: Specific localization of photosensitizers (PSs) to a certain organelle could result in targeted attack to cause greater trauma to cancer cells, eventually maximizing photodynamic therapy (PDT). However, currently, efficient and precise transportation of PSs via drug delivery to tumor cells and subcellular organelles is still challenging, due to a so‐called step‐reduction delivery dilemma (SRDD) which also threatens anticancer drug delivery to exert their efficacy. Herein, a cascade targeting near infrared II (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…1,2 With the rapid and excessive formation of reactive oxygen species (ROS), cell killing, microvascular damage effects and local immune responses were triggered through the lipid peroxidation and DNA damage, manifested as apoptosis, necrosis, or immunogenic cell death. [3][4][5][6][7][8] Over the past 30 years, PDT has been increasingly applied to treat various solid tumors, including brain, lung, gastrointestine, bone, bladder, prostate, breast, cervix, ovary, etc. 9,10 For the skin is the outermost layer of the body which is convenient for the irradiation of the light, Dermatology is a department with plenty of opportunities of PDT application, for the treatment of diseases from acne, naevus flammeus, to skin cancer.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 With the rapid and excessive formation of reactive oxygen species (ROS), cell killing, microvascular damage effects and local immune responses were triggered through the lipid peroxidation and DNA damage, manifested as apoptosis, necrosis, or immunogenic cell death. [3][4][5][6][7][8] Over the past 30 years, PDT has been increasingly applied to treat various solid tumors, including brain, lung, gastrointestine, bone, bladder, prostate, breast, cervix, ovary, etc. 9,10 For the skin is the outermost layer of the body which is convenient for the irradiation of the light, Dermatology is a department with plenty of opportunities of PDT application, for the treatment of diseases from acne, naevus flammeus, to skin cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] ICD is a particular modality of cell death that can be triggered by selective anticancer chemotherapeutics such as oxaliplatin (Oxa), [ 9 ] doxorubicin, [ 10 ] etc. photodynamic therapy (PDT), [ 11 ] and radiation therapy. [ 12 ] Tumor cells undergoing ICD can induce an adaptive anticancer immune response including the release or exposure of damage associated molecular patterns (DAMPs) by tumor cells that stimulate the attraction, activation and maturation of dendritic cells (DCs) and eventually the antigen‐specific priming of cytotoxic T lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] Results have shown that tumor cells undergoing type II ICD can release damage‐associated molecular patterns (DMAPs): calreticulin (CRT) exposed on their cell surface, adenosine triphosphate (ATP) secreted, and high mobility‐group protein box 1 (HMGB1) released. [ 13 ] Recent studies have shown that PDT could promote the apoptosis of tumor cells. Moreover, PDT could promote the uptake and presentation of tumor‐associated antigens by antigen‐presenting cells, reactivate the recognition and attack of tumor cells by T cells, and allow more infiltration of CD8 + T cells, thereby transforming immune “cold tumors” into immune “hot tumors” and finally improving the responses to immune checkpoint inhibitors.…”
Section: Introductionmentioning
confidence: 99%